Overview of Bone Marrow Aspiration from 120 Cats in Different Hematological Conditions - Thierry G. de Cristo; Giovana Biezus; Geanice Ledo; Marcela B. S. Teixeira; Mayara Vavassori; Denilson R. Soares; Mere E. Saito; Renata A. Casagrande (Veterinary Medicine International)
Bone marrow (BM) evaluation is highly important for the diagnosis of numerous hematological alterations in animals, especially cats, given their greater propensity for hematopoietic changes associated with retrovirus infections. This study aims to describe the main aspects of the BM of cats with different hematological conditions, comparing with reference intervals established from animals without hematological alterations and also with a previously established reference interval. To do so, we evaluated full blood and BM samples from 120 cats with no abnormalities on physical examination, negative for FeLV and FIV. Hemograms were performed from automated total cell and platelet and leukocyte differential counts in blood smears. BM samples were placed in Petri dishes; medullary spicules were selected to make up to eight cytological slides stained by the May–Grunwald–Giemsa technique, which were subjected to quantitative and cellular morphology evaluations. The cats were predominantly young, 64.2% female and 35.8% male. The average number of medullary spicules in samples was 13.7%, and density was 44%. In the BM quantitative analysis, prorubricytes and rubriblasts had higher quantities than the recommended one for all cats with or without hematological alterations. In all groups, lymphocytes were decreased, and cats with lymphocytosis were closest to the reference range, showing flame cells and Mott cells. The reference interval for the bone marrow cell count obtained from the samples in this work differs from previously established data, leading to different interpretations of the patient’s BM condition, according to the cell population observed and the reference interval used. This divergence strongly emphasizes the need to correlate clinical, epidemiological, hematological, and bone marrow data of each patient for a better understanding of the patient’s condition. The popularization of BM assessment is essential so that more reliable reference intervals can be established according to the population served by each pathologist and clinical laboratory.